Factors associated with condom use among men and women living with HIV in Lilongwe, Malawi: a cross-sectional study - Haddad, Lisa B (BMJ Sex Reprod Health, 2018)
BACKGROUND: Understanding the influences on condom use among men and women living with HIV is critical to tailoring sexually transmitted infection/HIV prevention efforts. METHODS: This is a sub-analysis of a cross-sectional survey including 255 women and 220 men who were sexually active, HIV-positive, and attending HIV care visits in Lilongwe, Malawi. We estimated adjusted prevalence ratios (aPRs) to evaluate for factors associated with consistent condom use (always using condoms in the past month) and use at last coitus for men and women in separate models. RESULTS: Among women: 38% and 55% reported consistent condom use and condom use at last coitus, respectively. For women, consistent use and use at last coitus were positively associated with the ability to refuse sex without condoms and shared decision-making compared with making the decision alone regarding condom use, and negatively associated with desire for children in the future. Consistent use also increased with longer antiretroviral therapy (ART) use (≥1 year compared with no ART use). Among men: 51% and 69% reported consistent condom use and condom use at last coitus, respectively. For men, the ability to refuse sex without condoms was associated with consistent use and use at last coitus, and believing that condoms should be used with other contraception was associated with consistent use. CONCLUSIONS: Our findings demonstrate ongoing low condom utilisation among HIV-positive individuals, and highlight that ART and contraceptive use do not deter condom use. Efforts to increase condom utilisation must recognise individual-level factors that influence use and should focus on relationship dynamics and promotion of empowerment and self-efficacy.